Evaluating hospital effectiveness and efficiency - García Barbero, M (Fondazione Smith Kline, 1997)
Proceedings of a WHO workshop that focused on evaluating hospital effectiveness and efficiency in Europe. Intended for professional public.
Keywords: Economics, Hospital; Hospital Administration; nemocnice; veřejné zdravotnictví; řízení nemocnice; Evropa; Efficiency, Organizational; ekonomika nemocniční; Europe; výsledky a postupy - zhodnocení (zdravotní péče); Hospitals; efektivita organizační; Outcome and Process Assessment, Health Care; management, organizace a řízení zdravotnictví